Comparing CSF amyloid‐beta biomarker ratios for two automated immunoassays, Elecsys and Lumipulse, with amyloid PET status - Eline A. J. Willemse; Betty M. Tijms; Bart N. M. vanBerckel; Nathalie Le Bastard; Wiesje M. van derFlier; Philip Scheltens; Charlotte E. Teunissen (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2021)
Abstract Introduction We evaluated for two novel automated biomarker assays how cerebrospinal fluid (CSF) amyloid beta (Aβ)1– 42‐ratios improved the concordance with amyloid positron emission tomography (PET) positivity compared to Aβ1– 42 alone. Methods We selected 288 individuals from the Amsterdam Dementia Cohort across the Alzheimer's disease clinical spectrum when they had both CSF and amyloid PET visual read available, regardless of diagnosis. CSF Aβ1– 42, phosphorylated tau (p‐tau), and total tau (t‐tau) were measured with Elecsys and Lumipulse assays, and Aβ1–40 with Lumipulse. CSF cut‐points were defined using receiver operating characteristic (ROC) for amyloid PET positivity. Results For both Elecsys and Lumipulse the p‐tau/Aβ1– 42, Aβ1– 42/Aβ1– 40, and t‐tau/Aβ1– 42 ratios showed similarly good concordance with amyloid PET (Elecsys: 93,90,90%; Lumipulse: 94,92,90%) and were higher than Aβ1– 42 alone (Elecsys 85%; Lumipulse 84%). Discussion Biomarker ratios p‐tau/Aβ1– 42, Aβ1– 42/Aβ1– 40, t‐tau/Aβ1– 42 on two automated platforms show similar optimal concordance with amyloid PET in a memory clinic cohort.